Physiotherapy Education in Libya: between Vocational and Higher Education - Muinr Krifa; Aziza Abdulkaber (AlQalam Journal of Medical and Applied Sciences, 2023)
This study aims to provide a comprehensive review of the current situation and challenges in physiotherapy education in Libya, with a specific focus on the disparities between higher education and technical education. The review primarily examines two key areas: the laws and regulations governing physiotherapy education, and the variations in curricula and years of study. In analyzing the laws and regulations, this study uncovers significant violations that have impacted the distinction between higher education and technical education in Libya. It highlights instances where technical education has assumed the role of higher education, leading to the issuance of higher degrees. Consequently, this has adversely affected the quality of the curriculum and the professional standing of the physiotherapy specialty. The conclusion of this review shed light on the implications of the blurred boundaries between higher education and technical education in Libya’s physiotherapy sector. It emphasizes the need for stricter adherence to regulations governing these educational pathways to ensure the maintenance of quality standards. Addressing these issues is crucial for safeguarding the integrity of physiotherapy education and improving the professional prospects within the specialty.